Mapping the landscape of research on workplace sexual discrimination: A bibliometric analysis - Sangadji, Suwandi S.; Hakim, Hakim; Rachman, Saiful (Universitas Islam Negeri Ar-Raniry, 2023)
Sexual discrimination in the context of the work environment is an adverse phenomenon where individuals are treated unfairly or unequally based on their gender or sexual orientation. This study aims to trace the evolution of the literature surrounding sexual discrimination in the workplace over time. Bibliometric methods were used in this study to review 298 research samples conducted between 1986 and 2023. The data was obtained from the Scopus database. The reason for using Scopus as the main reference data in this study is because the Scopus database is a citation and abstract index database that covers a wide range of scientific literature and focuses on various fields of science published worldwide in high-quality journals with comprehensive and representative data to accurately identify research trends and academic impact. Besides, the features provided by Scopus greatly facilitate in-depth bibliometric analysis. The focus of this study lies on scientific performance evaluation and literature mapping using Vosviewer and BibExcel tools. The research findings confirmed a significant increase in the number of publications and citations on this topic over the past five years. In addition, cross-disciplinary collaboration seems to have made an important contribution, involving the fields of health, law, psychology, as well as other social sciences. However, this study indicates the limitations of interdisciplinary cooperation in generating a more holistic and comprehensive understanding of this phenomenon.